Xanthogranulomatous salpingo-oophoritis associated with diverticular perforation - Bistees George; Cecilia G. Clement (Elsevier, 2021)
Xanthogranulomatous inflammation of the female genital tract is a rare entity with less than thirty cases being previously reported in the literature. It is characterized by destruction of the normal tissue followed by replacement with inflammatory cells and lipid- laden macrophages. In this report, we present a 55-year-old African American female with history of diverticulosis and use of intrauterine device, who presented with xanthogranulomatous inflammation extensively involving the fallopian tubes and ovaries, and concomitant diverticular perforation.